Oil extraction residue (OER) from end-of-life tire (ELT) recycling as a carbon black substitute for rubber products - Manuzon, Maria Janice D.; Diaz, Leslie Joy S. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
End-of-life tire (ELT) recycling can potentially turn waste into an immense and continuous source of valuable carbon black (CB). The recovery process entails precise pyrolysis conditions, and the recovered CB usually contain impurities that still require treatment. This study focused on the as-received and untreated CB recovered from recycled tires which were subjected to oil extraction, termed here as oil extraction residue (OER). Several studies have proven that the treatment of OER produces commercial grade CB. However, few of these utilize untreated OER for actual incorporation and testing in rubber products. Thus, the phys ical, chemical and mechanical properties of OER were investigated to determine its potential as a CB filler. Through darkfield microscopy, a reflective substance was observed on the OER surface which suggests the presence of wax or oiL Undecomposed elastomers were found based on the apparent surface texture after low magnification SEM. The morphology of OER under high magnification SEM had the characteristic aciniform structure of carbon black and the nanoparticle sizes of OER were also visually found to be wider in size distribution when compared with commercial carbon black sizes. Thermogravimetry confirmed the presence of organic and inorganic impurities through compositional analysis and results showed that OER contained 55.24% fixed carbon, 29.6% VOC, 1.87% moisture and 13.29% ash. XRD analysis also verified th at OER contains carbon black based on the amorphous graphitic carbon peaks at 2e = 25° and 43.3° corresponding to {002} and {100} / {101} planes, respectively. Zinc, Sulfur and Calcium were detected by SEM-EDS and XRF Spectroscopy, and XRD analysis suggests the possibility that some of these impurities are in the form of ZnO, ZnS and CaCO3. The fillers were then mixed into rubber and compounded using a specific tire formulation. The effect of using OER as a filler instead of commercial carbon black was investigated based on compound processability, cure characteristics and mechanical performance. First, the uncured compounds were subjected to processability tests and the results show that although the minimum Mooney viscosity of the OER substituted compounds are higher in value, they were not statistically different from the values of the compounds with commercial-CB-filled compounds. Cure characteristics of OER-filled compounds resulted to slower cure rate and longer scorch and cure times in comparison to commercial-CB-filled compounds by a difference of 1.75, 2.40 and 4.15 min, respectively. To determine if the present impurities were active as rubber additives, compensation was performed such that lower amounts of virgin ingredients were used to satisfy a given product formulation. Some impurities considered to be in the form of zinc oxide and organic sulfur normally incorporated into the compound were decreased and this resulted to faster cure rates. ΔS' values, which indicate extent of crosslink, were also calculated after using the Rubber Process Analyzer, and it was found that compensating for ZnO did not affect the extent of crosslinking while compensating for organic sulfur resulted to significantly lower amounts of crosslinks formed. These results show that there is a possibility that impurities in the form of ZnO may be used as an active ingredient in OER, or that its reduction induces lower thermal stability and induces faster heat spread although more replications and tests are recommended to prove this. OER was also compounded in increasing ratio of substitution. The samples were vulcanized and subjected to static (tensile) and dynamic (shear) mechanical testing. Compared to the tensile strength of vulcanized rubber with commercial CB (1874.11 ± 92.53 psi), full substitution using OER resulted to a tensile strength of 1205.65 ± 65 psi which is still close to the target value of 1200 psi. This significant decrease in strength is attributed to the larger filler dimensions of the OER which are less reinforcing, increasing amount of impurities and deactivation of active surface on CB brought about by presence of carbonaceous deposits on the OER surface. Thus, OER may be used as a CB substitute. The reduction of interaction between reinforcing fillers was measured using the RPA. Payne effect ΔG' values correlated to reinforcing filler interaction were found to decrease as more OER filler were incorporated in the rubber matrix. Consequently, increasing substitution of OER resulted to a decreasing trend in strength. ΔG' values for the cured compounds with 25% OER substitution were determined to be close to the values for commercial-CB-filled cured compounds. Thus, the most acceptable ratio for substitution was found to be 25% OER, giving tensile strength of 1555.42 ± 80.12 psi which is still within the defined boundaries for the product formulation to be able to perform satisfactorily in the target applicat
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Tires -- Recycl; Carbon-bl.; End-of-life tires